Simplification of Arabic Preparatory Classes through Daurah Mukatsafah in Higher Education - Riyadi, Slamet; Rozaanah, Rozaanah; Zaini, Hisyam (Institut Agama Islam Negeri Curup, 2023)
This research aimed to probe into the implementation of Daurah Mukatssafah program. As in introductory lens, the mastery of Arabic language competence is the primary basis for students taking study programs at tertiary institutions with Arabic as the language of instruction, both in Arab countries and abroad. Meanwhile, not all students have sufficient basic Arabic skills as an initial state to understand the materials presented in the classroom. As a solution, several tertiary institutions provide language preparation programs for students, but these must be completed within 1 to 2 years. The intensive learning model carried out for three months at the As-Sunnah Islamic College as a pilot program is thought to be able to replace the language preparation program with equally effective results. This research used a qualitative naturalistic approach where the research was carried out naturally following the program implemented in the field without manipulating the existing variables. Furthermore, the data were described and compared objectively with data from existing language preparation programs. Daurah Mukatssafah was carried out in two main activities. First, learning the Arabic book Baina Yadaik starting from volume 1 to 6, intensively in classes guided by several lecturers in each class. Second, language mastery used a language immersion model outside the classroom. The results found a significant increase in students' Arabic proficiency, equivalent to 1-year learning outcomes in the Language Preparation Class.